2018
DOI: 10.1017/ice.2018.176
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of automated disinfection with ozonated water in reducing sink drainage system colonization with Pseudomonas species and Candida auris

Abstract: Sinks in healthcare facilities are a potential reservoir for the dissemination of gram-negative bacilli and Candida spp. 1-4 Addressing sink contamination is challenging because sink drainage systems provide a favorable environment for pathogen colonization and biofilm formation, but they are not amenable to cleaning and disinfection. Disinfection of sinks with agents such as bleach, acetic acid, and hydrogen peroxide have been effective in some studies. 1,2 However, such approaches may be difficult to impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 8 publications
(5 reference statements)
1
11
0
1
Order By: Relevance
“…Although a recent study demonstrated C. auris resistance toward low concentrations and low exposure time of gaseous ozone [87], another study concluded a higher efficacy of repeated exposure of aqueous ozone, reducing the contamination of this yeast at a concentration range of 0.9-0.1 ppm [88], which is similar to the optimal concentration of 0.8 ppm in the present study. Considering this and the current efficacious use of dissolved ozone in many therapeutic and disinfecting procedures, ozonized tap water may be efficiently included in technologies for disinfection.…”
Section: Microbials' Morpho-structural Changes Upon Incubation Of Ozonized Tap Watersupporting
confidence: 77%
“…Although a recent study demonstrated C. auris resistance toward low concentrations and low exposure time of gaseous ozone [87], another study concluded a higher efficacy of repeated exposure of aqueous ozone, reducing the contamination of this yeast at a concentration range of 0.9-0.1 ppm [88], which is similar to the optimal concentration of 0.8 ppm in the present study. Considering this and the current efficacious use of dissolved ozone in many therapeutic and disinfecting procedures, ozonized tap water may be efficiently included in technologies for disinfection.…”
Section: Microbials' Morpho-structural Changes Upon Incubation Of Ozonized Tap Watersupporting
confidence: 77%
“…Many of the other methods used to control outbreaks related to sinks may be costly, labor intensive, and difficult to implement rapidly. These approaches have included placing barriers between sinks and work areas, 6 reducing water flow pressure, 6 ozonation of water, 18 heating and/or sonicating the drain stem, 9,[19][20][21] replacing the P-trap, 9,10,22 and complete elimination of sinks. 23 Another approach that could be implemented rapidly in outbreak settings is the use of disposable plastic sink drain covers that reduce dispersal of organisms from sink drains.…”
Section: Discussionmentioning
confidence: 99%
“…For oral decolonisation, 0.2% chlorhexidine mouthwash has been used, also chlorhexidine‐impregnated protective discs for central vascular catheter exit sites have been found effective to reduce line‐associated C. auris bloodstream infections . For decolonisation of C. auris in sink drainage systems, ozonated water has been effectively used . Compared to planktonic cells, C. auris biofilms showed reduced sensitivity to commonly used disinfectants such as povidone iodine, chlorhexidine and hydrogen peroxide …”
Section: Infection Prevention and Controlmentioning
confidence: 99%